Mechanical performance of concrete made with aggregates from construction and demolition waste recycling plants. (15th July 2015) - Bravo, Miguel; de Brito, Jorge; Pontes, Jorge; Evangelista, Luís
Abstract: This research aims at analysing the mechanical performance of concrete with recycled aggregates (RA) from construction and demolition waste (CDW) from various locations in Portugal. First the characteristics of the various aggregates (natural and recycled) used in the production of concrete were thoroughly analysed. The composition of the RA was determined and several physical and chemical tests of the aggregates were performed. In order to evaluate the mechanical performance of concrete, compressive strength (in cubes and cylinders), splitting tensile strength, modulus of elasticity and abrasion resistance tests were performed. Concrete mixes with RA from CDW from several recycling plants were evaluated, in order to understand the influence that the RA's collection point, and consequently their composition, has on the characteristics of the mixes produced. The analysis of the mechanical performance allowed concluding that the use of RA worsens most of the properties tested, especially when fine RA are used. On the other hand, there was an increase in abrasion resistance when coarse RA were used. In global terms, the use of this type of aggregates, in limited contents, is viable from a mechanical viewpoint. Highlights: Concrete with fine and coarse recycled aggregates (RA) from construction and demolition waste (CDW). CDW from five recycling plants with a wide variety of compositions. Analysis of the influence of the RA's source, composition, size and incorporation ratio. Proof of the feasibility of the use of these RA in terms of concrete's mechanical performance.